Front Cover: A Dendrite‐Structured RbX (X=Br, I) Interlayer for CsPbI2Br Perovskite Solar Cells with Over 15 % Stabilized Efficiency (ChemSusChem 20/2020). Issue 20 (28th September 2020) - He, Jingjing; Ge, Bing; Hou, Yu; Yang, Shuang; Yang, Hua Gui
Abstract : The Front Cover shows a dendrite‐structured RbX (X=Br, I) interlayer for CsPbI2 Br solar cells that realized power conversion efficiencies (PCE) over 15 % with a high open‐circuit voltage ( V OC ) of 1.27 V. This RbX interlayer could optimize the surface wetting behavior of TiO2 films and thus enabled the high quality of perovskite films. Interestingly, such a RbX dendrite‐structured interlayer also optimized the contact between perovskite and transport layer as well as passivated surface defects. More information can be found in the Full Paper by J. He et al .